2023
DOI: 10.56578/jimd020202
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Channel Supply Chain Pricing Decisions for Low-Carbon Consumers: A Review

Abstract: As environmental awareness grows, consumers' green and low-carbon preferences have become essential factors for market enterprises to consider in decision-making. This paper conducts a literature review of dualchannel supply chain pricing decisions under the influence of consumers' low-carbon preference. The analysis is carried out from two aspects: dual-channel supply chain types and consumers' low-carbon preference. By combining psychological games and analyzing relevant literature, this paper provides insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Platform companies create a conducive environment for communication among various participants in the supply chain and facilitate the transfer of knowledge and technology related to carbon reduction, thereby jointly creating products that meet green consumption demands ( Song et al ., 2023). This collaborative relationship leads to value co-creation effects in supply chain carbon reduction cooperation (Zhou et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Platform companies create a conducive environment for communication among various participants in the supply chain and facilitate the transfer of knowledge and technology related to carbon reduction, thereby jointly creating products that meet green consumption demands ( Song et al ., 2023). This collaborative relationship leads to value co-creation effects in supply chain carbon reduction cooperation (Zhou et al ., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…They can then use this data to understand customer behavior and market trends, focusing on adjusting future reverse logistics to optimize costs, reduce processing time, increase value for returned products, and better satisfy customer requirements (de Araújo et al, 2017). Also, results from recent research such as Song et al (2023) and Wang and Sun (2022) also indicated the increasing concern of customer on green consumption, thus referring to the increasing importance of reverse logistics.…”
Section: Reverse Logistics In E-commercementioning
confidence: 99%
“…Given the current circumstances, the researcher discovered that most purchase decisions would be based on behavioral patterns like seeking the best value for money, looking for alternative purchase channels, prioritizing quality and convenience, and upholding social and environmental values. Based on the established patterns of consumer behavior, companies can adapt their marketing and sales strategies to better align with the intentions of their audience, as noted by Song et al [29], and promote sustainable consumption, as suggested by Arora and Mishra [30].…”
Section: Literature Reviewmentioning
confidence: 99%